THE IMPACT OF INBOUND MARKETING ON DIGITAL CONSUMER BEHAVIOR IN ALGERIA - TELILANI, Ghozlan; BOUTEDJA, Djamel (Studia Universitatis Babeș-Bolyai Oeconomica, 2024)
This research study aims to measure the impact of inbound marketing on digital consumer behavior. The researchers collected data from 126 participants who are customers of the startup Nrecycli. The researcher used structural equation modeling (SEM) through Smart PLS 4 software to analyze the data. The findings of this study indicated that the role played by inbound marketing processes (attraction, conversion, closure, and delight) on digital consumer behavior was strong and influential. The results also indicated a positive relationship between inbound marketing, increased consumer engagement and loyalty to the institution. JEL classification: M30, M31, M37, M13